The Relationship Between Music Engagement And Ethical Decision-Making Among The Owner Manager In Service Sector - Chua, Chong Tat (2018)
Ethical decisions are crucial in business or any profit-making organizations as these decisions affect the income. The quality of decisions is often affected by several factors such as music engagement, locus of control, personal spiritual belief, and personal ethics. The ethical problems were reported at 37% in Nation and this motivated a momentum in more research in business ethics in Malaysia. There was also lack of empirical studies done in ethical decision-making. The purposes of this study aims to examine the interrelationship between music engagement, personal spiritual belief, personal ethics, locus of control and ethical decision-making. The direct relationships of; i) music engagement and ethical decision-making, ii) personal spiritual belief and ethical decision-making, and iii) personal ethics and ethical decision-making were examined. The indirect relationships of personal ethics as the mediator on the relationships between music engagement and ethical decision-making as well as personal spiritual belief and ethical decision-making were examined. Besides, the locus of control was tested as a moderator on the relationships between personal ethics and ethical decision-making. Rest (1986) model and ethical theories were used to support the whole research framework. The unit of analysis in this study was owner manager in service sector of SMEs. The purposive sampling technique was employed in the data collections. A total of 273 samples were collected throughout this research.